PENGARUH CAPITAL ADEQUACY RATIO (CAR), RETURN ON ASSET (ROA), DAN LOAN DEPOSIT RATIO (LDR) TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2021 - Astuti, Metyka Puji; Rahayu, Sri; Suryatama, Fajar (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2024)
The share price is largely determined by the supply and demand for shares. This study aims to examine the effect of Capital Adequacy Ratio (CAR) on stock prices in banking companies listed on the Indonesia Stock Exchange in 2014- 2021, test the effect of Return On Assets (ROA), on stock prices in bankingcompanies listed on the Indonesia Stock Exchange For 2014-2021, test the effect of the Loan Deposit Ratio (LDR) on stock prices in banking companies listed on the Indonesia Stock Exchange for 2014-2021, and test the effect of Capital Adequacy Ratio (CAR), Return On Assets (ROA), and Loan Deposits Ratio (LDR) to stock prices in banking companies listed on the Indonesia Stock Exchange in 2014-2021.The analytical tool used in this study is multiple linear regression analysis with a total population of 46 banking companies listed on the Indonesia Stock Exchange. This study used a sample of 18 banking companies listed on the Indonesia Stock Exchange in 2014-2021 with a total of 144 data. The type of research used in this research is associative quantitative. Data processing using the SPSS version 23 program with data testing techniques classic assumption test, correlation test, regression test, coefficient of determination test, partial hypothesis testing (t test) and simultaneous hypothesis testing (F test).The results of the analysis of the Capital Adequacy Ratio (CAR) variable yield tcount (-0.114) > ttable (-1.97705), then H0 is accepted and Ha1 is rejected and the significance value is (0.909 > 0.05). The results of the analysis of the Return On Assets (ROA) variable yield tcount (4.743) > ttable (1.97705), then H0 is rejected and Ha2 is accepted and the significance value is (0.000 <0.05). The results of the analysis of the Loan Deposit Ratio (LDR) variable yield tcount (-0.243) < ttable (- 1.97705), then H0 is accepted and Ha3 is rejected and the significance value is (0.808 > 0.05). Based on the F test, the results of Fcount were 7.557 > Ftable 2.67 with a significance level of 0.000 <0.05, so it was concluded that H0 was rejected and H1 was accepted.Keywords : Stock Price, Capital Adequacy Ratio CAR), Return On Assets (ROA), Loan Deposit Ratio (LDR)